Wystąpienie państwa członkowskiego z Unii Europejskiej w świetle art. 50 TfUE na przykładzie Wielkiej Brytanii - Butyter, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
In the article the issue of withdrawal procedures of a Member State from the structure of the European Union is presented. For a better understanding of the problem of exit procedure, which in accordance with Article 50 TFEU is an integral part of the membership in the EU, is compared to other possible options of withdrawal from the EU. Also the example of Great Britain, whose citizens decided in a referendum to withdraw from the EU and actually initiated the first attempt at withdrawal from the European Union is presented. The main goal of the article is to present scenarios of future relations between the EU and the UK, as well as an attempt to predict future effects, which will take place in case of withdrawal of the United Kingdom from the EU. Scenarios and effects in general are similar for other countries of the European Union if they ever decide to withdraw from the EU.
Keywords: European Union; Member States; TFEU; withdrawal from the EU; Brexit